Engineered Nanomedicine with Alendronic Acid Corona Improves Targeting to Osteosarcoma - Nguyen, Thi D.T.; Pitchaimani, Arunkumar; Aryal, Santosh (My University, 2016)
We engineered nanomedicine with the stealth corona made up of densely packed bone seeking ligand, alendronic acid. In a typical nanoconstruct, alendronic acid is conjugated with hydrophilic head moiety of phospholipid that has an ability to self-assemble with hydrophobic polymeric core through its hydrophobic long carbon-chain. Proposed nanomedicine has three distinct compartments namely; poly(l-lactic-co-glycolic acid) polymeric core acting as a drug reservoir and skeleton of the nanoconstruct, phospholipid monolayer covers the core acting as a diffusion barrier, and a densely packed alendronic acid corona acting as a stabilizer and targeting moiety. Thus engineered nanomedicine attain spherical entity with ~90 ± 6 nm having negative zeta potential, −37.7 ± 2 mV, and has an ability to load 7 ± 0.3 wt% of doxorubicin. In-vitro bone targeting efficiency of nanomedicine was studied using hydroxyapatite crystals as a bone model, and found significant accumulation of nanoparticle in the crystals. Moreover, cellular internalization studies with mouse osteosarcoma confirm the selectivity of nanomedicine when compared to its internalization in non-targeted mouse melanoma. This nanomedicine shows prolong stability in serum and deliver the drug into the cell exhibiting an IC50 of 3.7 μM. Given the strong interacting property of alendronic acid with bone, the proposed nanomedicine hold promises in delivering drug to bone microenvironment.
Citation: Nguyen, T. D. T., Pitchaimani, A., & Aryal, S. (2016). Engineered Nanomedicine with Alendronic Acid Corona Improves Targeting to Osteosarcoma. Scientific Reports, 6, 36707.
Keywords: Bone cancer; Drug delivery